Gender Justice in Workplace Sexual Harassment Law Enforcement - Alya Miladina Fatima Baranyanan; Mufti Khakim (Jurnal Cakrawala Hukum, 2026)
Despite the legal protections established by Law Number 12 of 2022 (UU TPKS), female employees remain highly susceptible to various forms of workplace sexual harassment, severely compromising their psychological health and career progression. This study evaluates the integration of gender justice principles within the enforcement of sexual violence laws. Utilizing a normative-empirical methodology, the research synthesizes legal doctrine with practical field data through statutory and socio-legal approaches. Primary insights were gathered from interviews with Legal Aid Institutions (LBH) and advocacy groups, supplemented by a comprehensive review of primary and secondary legal sources. Through qualitative normative analysis, the study concludes that systemic power imbalances, entrenched patriarchal norms, and insufficient legal literacy continue to hinder the effective implementation of current protective frameworks. This study contributes a socio-legal framework that maps the gap between normative mandates in the TPKS Law and ground-level enforcement practices, offering concrete recommendations for institutional reform in workplace sexual harassment handling.